Metacognitive Therapy for Adjustment Disorder in a Patient With Newly Diagnosed Pulmonary Arterial Hypertension: A Case Report - Winter, Lotta; Naumann, Franziska; Olsson, Karen; Fuge, Jan; Hoeper, Marius M.; Kahl, Kai G. (Frontiers in Psychology, 2020)
Adjustment disorders (ADs) belong to the worldwide most diagnosed mental disorders and are particularly frequent in patients with an underlying physical illness. Pulmonary arterial hypertension (PAH) is a severe and disabling disease, which significantly impacts on quality of life and has high mortality rates. The authors here present the case of a young female who developed a severe adjustment disorder with both anxious and depressive symptoms after a diagnosis of PAH requiring intensive care treatment due to right heart failure. Psychosocial functioning was severely impaired, and physical health reduced. Following hemodynamic stabilization and the establishment of PAH treatment, the patient was admitted to the Department of Psychiatry, Social Psychiatry and Psychotherapy and received metacognitive therapy (MCT). AD with mixed anxiety and depressed mood was diagnosed according to DSM-V criteria. At the start of treatment she reported significant mental distress, indicated by a total sum score of the Hospital Anxiety and Depression Scale (HADS) of 20 points. The 6 min walking distance was only 358m before the patient was exhausted. She then was treated with MCT without further psychopharmacological drugs. After only four MCT sessions, she fully remitted from AD which was accompanied by a 11 point reduction in the HADS (to 9 points). MCT specific scores also improved (MCQ-30 sum score decreased from 77 to 35). Notably physical capacity improved as well, documented by an improved walking distance (439m; +22%). This is the first case of a patient with AD in the context of PAH who was treated with MCT. The case report suggests that MCT is a possible psychotherapeutic treatment option for AD in the context of a potentially life threatening disease. The study design does not permit an attribution of outcome to MCT but it suggests MCT is a potentially viable and acceptable treatment option.